Teachers’ Reflective Practice in Lesson Study: A Tool for Improving Instructional Practice - Gutierez, Sally Baricaua (Alberta Journal of Educational Research, 2016)
In teacher education, a collection of research has established the importance of reflection in professional development. Lesson study, a popular professional development in Japan, incorporates reflection in one of its stages to enhance teachers’ capacity to look into their enacted practices to improve their research lessons. However, there appear to be few studies determining the types of reflective practice among teachers. In this study, the various stages of lesson study process were documented and transcribed to analyze the teachers’ reflective practices. Qualitative analyses yielded three types of reflective practice exemplified by the teachers, namely: descriptive, analytical, and critical. The study highlighted the collaborative, sustainable, and provisional environment which enabled the teachers to become practitioners who are able to use their reflections to gain understanding of their instructional practices. Findings also indicated that the context of professional development for teachers must be tailored to their direct experiences for them to significantly use the outcomes. La recherche en formation des enseignants a établi l’importance de la réflexion dans le développement professionnel. L’étude de cours, qui constitue un élément important du développement professionnel au Japon, intègre la réflexion et vise à augmenter la capacité chez les enseignants de se pencher sur leurs pratiques pour améliorer leurs leçons. Toutefois, il semble avoir peu d’études portant sur le type de pratique réflexive qu’entreprennent les enseignants. La documentation et la transcription des différentes étapes du processus de l’étude de cours ont permis d’analyser les pratiques réflexives chez les enseignants. Les analyses qualitatives en ont révélé trois types : descriptives, analytiques et critiques. Cette étude met en évidence le milieu collaboratif, provisoire mais durable, qui a permis aux enseignants de puiser dans leurs réflexions pour mieux comprendre leurs pratiques pédagogiques. Les résultats ont également indiqué que pour que les enseignants profitent de façon significative de leur développement professionnel, le contexte doit être adapté à leurs expériences directes.